(2/m-2-8/m2-4-1/m+2)(m2+4m+4) выражение

сырнаядуша сырнаядуша    2   05.09.2019 02:10    0

Ответы
aleksbotalov33p00u0t aleksbotalov33p00u0t  26.08.2020 15:21
Решим по действиям:
1) 2/(m - 2) - 8/(m² - 4) = 2/(m - 2) - 8/(m - 2)(m + 2) = 2(m + 2)/(m - 2)(m + 2) -
8/(m - 2)(m + 2) = (2m + 4 - 8)/(m - 2)(m + 2) = (2m - 4)/(m - 2)(m + 2) =
2(m - 2)/(m - 2)(m + 2) = 2/(m + 2)
2) 2/(m + 2) - 1/(m + 2) = 1/(m + 2)
3) 1/(m + 2)·(m² + 4m + 4) = (m + 2)²/(m + 2) = m + 2
ответ: m + 2. 
ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Алгебра